Palliation in pediatric otorhinolaryngology. (October 2018) - Shah, Udayan K.; Miller, Elissa G.; Levy, Carly
Abstract: Palliation in pediatric otorhinolaryngology is a rarely discussed but important aspect of care. This review encapsulates current thinking on pediatric palliative care (PC) and demonstrates, through one case, the impact of integrating PC into clinical care. We encourage early consideration of pediatric palliative care approaches for children with complex otorhinolaryngologic disorders.